(untitled) - Grumbine, R. Edward (London, 2010)
Where the Dragon Meets the Angry River is an incisive look at the possible fates of China and the planet. Will the Angry River continue to flow? Will Tibetan girls from subsistence farming families learn to read and write? Can China and the United States come together to lead action on climate change? Far-reaching in its history and scope, this unique book shows us the real-world consequences of conservation and development decisions now being made in Beijing and beyond.
Keywords: Khía cạnh môi trường,Water resources development; Phát triển nguồn tài nguyên nước,Enviromental aspects; Trung Quốc,China